Estrategias metodológicas y su aporte en el aprendizaje significativo de los estudiantes de séptimo semestre de la Carrera de Psicología 2022 - Murillo Benavidez, Denisse Dayana (2022)
The present research work under the theme methodological strategies and the contribution in meaningful learning, has been carried out under the aim of analyzing the incidence of methodological strategies in the significant learning of students who reside in the psychology career precisely studying the seventh semester, it was raised under a descriptive-quantitative design, to accurately determine the percentage of study obtained, for which a survey was carried out that was deployed to the 31 students who made up the previously designated classroom, reaching the conclusion through the deduction Based on the numbers obtained, the methodologies applied in them do not contribute much to meaningful learning, for which it is recommended to organize classes, improve active participation, provide problem-solving methods that can better integrate into the professional field. through its sporadic intervention and that it seizes ex experience on the proper management of psychological processes, also improve the aspect of insecurity shown in some students, through an action plan in which students take center stage, in psychology the student must have a very critical knowledge that helps him discern the possible negative factors that are found in the patients that you will have to address in your professional career.